2016
DOI: 10.17795/modernc.8849
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Grape Seed Extract Ointment on Approximation of Cesarean Section Wound

Abstract: Background: Cesarean section is among the most important gynecological surgeries and is the most common surgery in the present era. Delayed wound healing is among the main post-cesarean complications. It dramatically affects female's quality of life and causes frequent medical visits and even re-hospitalization. Objectives: This study aimed at investigating the effects of grape seed extract on the approximation of cesarean section wound. Methods: This double-blind randomized controlled trial was done during ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The findings of their clinical study indicate that they have used 5 % ointment of GSE on caesarean section (CS). They observed that it accelerates wound healing and reduce its closure time [31]. The findings of all these reported studies confirms that they have used about 2-5 % of GSE without using any polymer.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…The findings of their clinical study indicate that they have used 5 % ointment of GSE on caesarean section (CS). They observed that it accelerates wound healing and reduce its closure time [31]. The findings of all these reported studies confirms that they have used about 2-5 % of GSE without using any polymer.…”
Section: Introductionmentioning
confidence: 54%
“…PCs also helps in promoting the formation of collagen and elastin and preservation of skin moisture. Furthermore, PCs induces vascular endothelial growth factor, reduces edema and encourages blood flow thereby accelerates wound healing [28][29][30][31][32][33]. Khanna et al reported the outcome of grape seed extract (GSE) on in-vivo wound healing among nine male BalbC mice.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers were asked to apply 1 g of ointment on the post-cesarean wound site every 12 hours. The wound site was evaluated at 6 and 14 days after the intervention, which showed a statistically significant difference between the three groups (p = 0.02) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%